Brand Characteristics, Perceived Quality of Freemium Users, and Premium Service Purchase Intention: The Case With Netflix Users - Dogan, Sahika (IGI Global, 2024)
The rising popularity of online video streaming services challenge the dominancy of traditional television channels due to changing television viewing trends, as personalized individual services have also been integrated into online video streaming. This study aims to explore potential relationships between brand related characteristics, perceived quality and purchase intention among freemium online video streaming service users in the context of Netflix. Considering the changes in television viewing trends and the impressive amount of revenue drawn by the Netflix company from the Turkish audience, it is important to reveal which factors encourage free users to purchase paid membership. Findings revealed significant relationships between brand image, components of perceived quality (user friendliness, visual design, operation speed and safety) and purchase intention; while it was found that brand loyalty does not impact on users’ purchasing decisions. © 2025 by IGI Global Scientific Publishing. All rights reserved.
Keywords: Brand Image; Freemium; Individual Service; Netflix; Online Video Streaming; Perceived Quality; Purchase Intention; Television Channel; Turkishs; Video Streaming Services